CITY BRANDING : SEBUAH TINJAUAN METODOLOGIS DENGAN PENDEKATAN ELABORATIF, PRAKTIS, DAN ILMIAH - Ayyub Ashari Sukmaraga; Aditya Nirwana (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2016)
City branding is a one way to establish the city competitiveness, and currently, the main focus and the most pressing needs. The need for a regional/city brand, will make the the region has a strong positioning, especially in the field of global tourism. With elaborative approach to the theories of branding, marketing management, semiotics and aesthetics, this paper aims to describe a handy and scientific method of city branding. From these elaborative approach, it can be concluded a city branding method that consists of 5 stages: 1) Determine the city's core brand value by first outlining potential values owned by the city, with involving internal stakeholders; 2) Determine the city's core brand message, by the way look at the gap between the perception of the city with the reality of the city, which is carried out with the involvement of external stakeholders; 3) Determine the personality of the city, with the potential to describe the personality of the city, and then determine the personality core, this is done by engaging internal stakeholders; 4) Determine the brand icon of the city, consisting of two approaches, there is formal approaches (aesthetic), and the semiotic approach centered on the content; and the last is 5) Designing brand roadmap.